Automatic imitation in a rich social context with virtual characters - Pan, Xueni; Hamilton, Antonia F. de C. (Frontiers in Psychology, 2015)
It has been well established that people respond faster when they perform an action that is congruent with an observed action than when they respond with an incongruent action. Here we propose a new method of using interactive Virtual Characters (VCs) to test if social congruency effects can be obtained in a richer social context with sequential hand-arm actions. Two separate experiments were conducted, exploring if it is feasible to measure spatial congruency (experiment 1) and anatomical congruency (experiment 2) in response to a virtual character, compared to the same action sequence indicated by three virtual balls. In experiment 1, we found a robust spatial congruency effect for both VC and virtual balls, modulated by a social facilitation effect for participants who felt the VC was human. In experiment 2 which allowed for anatomical congruency, a form by congruency interaction provided evidence that participants automatically imitate the actions of the VC but do not imitate the balls. Our method and results build a bridge between studies using minimal stimuli in automatic interaction and studies of mimicry in a rich social interaction, and open new research venue for future research in the area of automatic imitation with a more ecologically valid social interaction.